Strengthening farmer-managed seed systems in South Africa - Sema, Ramadimetja Precious; Matelele, Lehlogonolo Abner; Maluleke, Nkat Lettie; Phora, George; Mokoena, Mpolokeng Lydia; Netnou-Nkoana, Noluthando Caroline; Bairu, Michael Wolday; Gerrano, Abe Shegro; Khoza, Lindiwe; Shargie, Nemera; Vernooy, Ronnie (2023)
This report presents field activities carried out in the period 2019-2022 in support of farmer-managed seed systems in South Africa, in particular the conservation efforts and participatory variety selection (PVS) carried out by the community seed banks of Gumbu, Jericho and Sterkspruit. The PVS was done on four priority crops selected by the farmers, cowpea, okra, pearl millet and sorghum, with the support of DALRRD and the Agricultural Research Council - Vegetable, Industrial and Medicinal Plants (ARC-VIMP; formerly ARC-VOPI) campus at Roodeplaat (Gauteng), and the ARC-Grain Crops (ARC-GC) campus at Potchefstroom (North West Province). The report also presents a synthesis of results achieved since the start of the activities and identifies challenges encountered.